Pengaruh Penerapan Media Pohon Literasi Terhadap Kemampuan Berpikir Kritis Peserta Didik Kelas V SDN 2 Way Lima Kabupaten Pesawaran - Atika, Fina Dina; Tohir, Ahmad; Soraya, Rahayu (UNIVED Press, Universitas Dehasen Bengkulu, 2023)
This study aims to determine whether there is an effect of applying learning media using literacy trees on the critical thinking skills of fifth grade students at SD Negeri 2 Way Lima, Pesawaran District. This research is a quantitative research with the type of pre-experimental design that uses the form of one group pre-test post-test design. The population in this study were fifth grade students at SD Negeri 2 Way Lima, Pesawaran Regency. Determination of the sample with saturated sampling technique. Data collection techniques and data collection instruments using observation, documentation and testing techniques. The data analysis technique used was the t-test (paired sample t test) for the same sample with different treatments (pre-test post-test) with tcount < ttable with a value of 0.003 <0.05. This proves that there is an effect of applying literacy tree media to the critical thinking skills of fifth grade students at SD Negeri 2 Way Lima, Pesawaran Regency.